Effect of laser beam angle of incidence on surface roughness and porosity of IN718 parts manufactured via laser powder bed fusion - Tolvanen, Einari (My University, 2024)
Laser powder bed fusion of metal (PBF-LB/M) is a rapidly evolving digital manufacturing technology paving the way for a new industrial revolution. It has attracted attention in industry and academia thanks to its ability to produce complex geometries, while maintaining cost-efficiency in low-volume production. The utilization of laser beam in layer-by-layer fusion of metal powder induces certain challenges related to the quality of the manufactured components. In recent years, researchers have reported variations in defect formation depending on the location of the manufactured components on the build platform. Several explanations have been provided for these variations, one of which is the laser beam angle of incidence (LBAI), which varies across the build platform. The aim of this thesis is to investigate the effect of LBAI on surface roughness and porosity of Inconel 718 (IN718) parts manufactured via PBF-LB/M. The proposed part characterization methodology can be used as a benchmark in process development that aims to mitigate the formation of the studied defects. Experiments were conducted by characterizing the laser beam and by fabricating different geometries at different build platform locations. Surface roughness and porosity was analyzed from the fabricated test parts. Results in the current work indicate that the laser beam spot is prone to elongation when the LBAI is increased, which can lead to loss of energy density at the spot periphery. Surface roughness characterization demonstrated that the effect of LBAI depends on the surface orientation in relation to the laser beam incidence. Based on the findings, it is anticipated that the laser beam that is aligned parallel to the fabricated surface yields the most optimal surface roughness. Porosity characterization showed that the effect of LBAI is negligible when using parameters that are optimized to yield fully dense parts. On the contrary, parameters that yielded lack of fusion showed distinct increase in porosity when LBAI was increased. Additionally, opportunities for future research were identified, which includes the effect of laser beam scanning strategy and the effect of inert gas flow conditions across the powder bed.
Keywords: Laser powder bed fusion, direct metal laser sintering, selective laser melting, additive manufacturing, Inconel 718, 3D printing, angle of incidence, surface roughness, lack of fusion, porosity